2004
DOI: 10.1207/s15328007sem1103_6
|View full text |Cite
|
Sign up to set email alerts
|

Divorce and Child Behavior Problems: Applying Latent Change Score Models to Life Event Data

Abstract: Effects of parents' divorce on children's adjustment have been studied extensively. This article applies new advances in trajectory modeling to the problem of disentangling the effects of divorce on children's adjustment from related factors such as the child's age at the time of divorce and the child's gender. Latent change score models were used to examine trajectories of externalizing behavior problems in relation to children's experience of their parents' divorce. Participants included 356 boys and girls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 51 publications
8
55
1
4
Order By: Relevance
“…However, some research supports the notion that gender and age may have significant effects on children"s general adjustment to divorce, with boys scoring moderately higher than girls on externalising behaviours, while the opposite is true for internalising behaviours (Amato, 2001;Amato & Keith, 1991;Malone et al, 2004;Rodgers & Rose, 2002). In a study done by Malone et al (2004), it was found that boys who were in elementary school when their parents divorced, showed an increase in externalising behaviour problems in the year of the divorce, which continued in the years thereafter.…”
Section: Internalising and Externalising Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some research supports the notion that gender and age may have significant effects on children"s general adjustment to divorce, with boys scoring moderately higher than girls on externalising behaviours, while the opposite is true for internalising behaviours (Amato, 2001;Amato & Keith, 1991;Malone et al, 2004;Rodgers & Rose, 2002). In a study done by Malone et al (2004), it was found that boys who were in elementary school when their parents divorced, showed an increase in externalising behaviour problems in the year of the divorce, which continued in the years thereafter.…”
Section: Internalising and Externalising Problemsmentioning
confidence: 99%
“…Malone, Lansford and Castellino (2004) have found that children who have experienced the life event of a divorce are at high risk for exhibiting both internalising and externalising problems. According to Hetherington (1999), the extent of risk for divorced children is at least twice that of children from continuously married parents, with the largest effects seen in externalising symptoms, such as conduct disorders, anti-social behaviour and problems with authority figures and parents (Kelly & Emery, 2003).…”
Section: Internalising and Externalising Problemsmentioning
confidence: 99%
“…Malone et al 55 apontam as crianças do sexo masculino que vivem a separação parental como as que registram mais comportamentos de externalização na escola, sobretudo no ano da separação parental, com uma descida até os níveis basais um ano após a ruptura conjugal, comparativamente às crianças do sexo feminino. Essas condutas são habitualmente associadas a baixos níveis de produção de cortisol.…”
Section: Problemas De Internalização E Externalização: Uma Perspectivunclassified
“…Este mesmo meio, rico em estressores susceptíveis de cronicidade, facilmente interfere na resposta fisiológica ao estresse, o que, por sua vez, tem impacto na saúde física 79 e psicológica da criança 46,55 .…”
Section: Tabela 2 -Principais Conclusões Sobre O Impacto Da Separaçãounclassified
“…The high number of divorced families over the past decade has raised concern regarding the effect of divorce on children and adolescents (Amato, 2000;Kelly, 2003;Hetherington, 2003;VanderValk et al, 2004). Researchers have found that parental divorce place children and adolescents at greater risk of adjustment problems (Amato & Keith, 1991;Amato, 2000;Kelly, 2000;Hetherington, 2003;Kelly & Emery, 2003: Dimitrieva et al, 2004: Santrock, 2007 especially externalizing problems such as aggression, antisocial behavior problems and delinquency, and internalizing problems such as depression, anxiety and self-esteem and low level of academic performance (Hetherington et al, 1993;Amato, 2001;Malone et al, 2004;Demuth & Brown, 2004;Lansford et al, 2006). Studies in recent decade has focused on understanding the processes by which parental divorce affects children and identifying a variety of protective and vulnerability factors which moderate or mediate these effect.…”
Section: Introductionmentioning
confidence: 99%